1995
DOI: 10.1164/ajrccm.152.1.7541278
|View full text |Cite
|
Sign up to set email alerts
|

Clara cell protein (CC-16) induces a phospholipase A2-mediated inhibition of fibroblast migration in vitro.

Abstract: Clara cell protein (CC-16, also designated CC-10) is synthesized by the bronchiolar epithelium and has been suggested as an inhibitor of phospholipase A2 (PLA2) activity. Therefore, CC-16 is a candidate for controlling inflammatory events in the lung. Because CC-16 amounts and function may be altered in fibrosing lung diseases in which bronchiolar injury has been reported, it was measured in alveolar fluids and sera. Secretory PLA2 activity in alveolar fluids and the influence of CC-16 on platelet-derived grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
1
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 0 publications
4
118
1
5
Order By: Relevance
“…61 Interestingly, CCSP can also suppress fibroblast migration. 62 Additionally, stressed airway epithelial cells release profibrotic factors that can induce a remodeling response by fibroblasts, 63 and delayed lung epithelial repair promotes fibroblast proliferation. 64,65 Thus, evidence is mounting that epithelial damage promotes fibroproliferation.…”
Section: Discussionmentioning
confidence: 99%
“…61 Interestingly, CCSP can also suppress fibroblast migration. 62 Additionally, stressed airway epithelial cells release profibrotic factors that can induce a remodeling response by fibroblasts, 63 and delayed lung epithelial repair promotes fibroblast proliferation. 64,65 Thus, evidence is mounting that epithelial damage promotes fibroproliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Even micromolar concentrations of CC16 have been shown to inhibit chemotaxis of neutrophils and monocytes (Laing et al 1998). The protein is known to control the proliferation and migration of fibroblasts in the lungs (Lesur et al 1995). In addition, it also inhibits the activity of secreted and intracellular phospholipase A 2 , thereby limiting the synthesis of prostaglandins and leukotrienes (Levin et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…CC10 also inhibits fibroblast chemotaxis, which is related to a blockage of the secretory phospholipase A 2 (PLA 2 ; Ref. 17). Similarly, studies have suggested that CC10 is able to modulate the activity of IFN-␥ (18).…”
mentioning
confidence: 97%